Efficacy of a phone application on treatment adherence in asthmatic patients in Upper Egypt - Entsar H. Mohamed; Heba M. Mohammed; Mohammad G. A. Khalaf (The Egyptian Journal of Bronchology)
Abstract Background Over 339 million people worldwide suffer from asthma, a common and chronic illness affecting the airways. Treatment adherence is generally poor, with rates of less than 50% for children and 30–70% for adults. As smartphone usage continues to rise globally, mobile health (mHealth) technologies hold promise for enhancing self-care among asthma patients by offering support services such as information, educational resources, and behavior modification reminders. Objective To evaluate the role of a mobile application in reminding the patient to take his medication and the effects of this on quality of life, asthma control, and treatment adherence. Methods This is a randomized controlled clinical trial that included 264 asthmatic patients presenting to the outpatient clinic. Patients were randomized to a control group with usual asthma care and an intervention group that used an asthma reminder. Asthma Control Test, Morisky Medication Adherence Scale, and quality-of-life questionnaire were assessed in the previous and the following 3 months of usage. Results This study included 264 asthmatics (132 patients in the intervention group, 132 patients in the control group). During the follow-up visit after 3 months of randomization, there was a statistically significant higher mean of asthma-control tests (P-value < 0.001), adherence score (P-value < 0.001), and quality-of-life questionnaire (P-value < 0.001) among the intervention group compared to the control group. Also, there were significantly lower exacerbations and hospitalizations (P-value = 0.036) in the intervention group. Conclusion Our study indicates that smartphone apps are an effective way to improve asthma control and treatment adherence. Poor adherent patients with chronic diseases must be encouraged to download a smartphone application that supplies information and reminds them about treatment on time. Trial registration ClinicalTrials.gov ID: NCT06233123.